Atrial Fibrillation, Venous Thromboembolism, and Risk of Pulmonary Hypertension: A Swedish Nationwide Register Study - Clara Hjalmarsson; Martin Lindgren; Niklas Bergh; Björn Hornestam; J. G. Smith; Martin Adiels; Annika Rosengren (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atrial fibrillation (AF) is suggested to be associated with venous thromboembolism (VTE) and might thereby play a role in the development of chronic thromboembolic pulmonary hypertension (PH). By elevating left‐sided filling pressure and promoting atrial myopathy, AF may also play a role in the development of postcapillary PH. We aimed to investigate the association between AF, with or without incident VTE, and the occurrence of PH. Methods A total of 521 988 patients diagnosed with AF between 1987 and 2013, without a previous diagnosis of VTE or PH, were identified from the Swedish National Patient Register and matched for age, sex, and county with 1 017 277 population controls without AF, VTE, or PH. Results The mean age of the patients with AF was 71.1 (SD ±10.1) years and 42.8% were women. During a median follow‐up period of 11 (interquartile range 5.1–17) years, 4454 (0.9%) patients with AF, and 1855 (0.2%) controls were diagnosed with PH, hazard ratio 4.7 (4.4–5.0). The AF group had a significantly higher comorbidity burden at baseline, with a mean CHA2DS2‐VASc of 2.9 compared with 2.1 in controls. In the absence of intercurrent VTE, the hazard ratio of PH was 4.2 (3.9–4.5) among patients with AF compared with controls. Intercurrent VTE increased the hazard ratio of PH a further 1.9‐fold (1.7–2.1) and 3.5 (3.1–4.0), among patients with AF and controls, respectively. The hazard ratio for PH in patients with AF with incident VTE was 8.1 (7.3–9.1). Conclusions AF was associated with a markedly increased risk of developing incident PH, and this risk was further increased by incident VTE.